2014
DOI: 10.1007/s13593-014-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from conventional and organic cropping systems in Spain. I. Herbaceous crops

Abstract: Agriculture is a major driver of climate change, particularly when all indirect emission sources are accounted for. Mitigation options targeted on one process are often proposed, ignoring their secondary effects on the overall greenhouse gas balance. Integrative methodologies such as life cycle assessment (LCA) are often applied without adjusting emission factors to specific site characteristics. Here, we used LCA to calculate the global warming potential of 38 pairs of organic and conventional herbaceous crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 26 publications
5
38
0
1
Order By: Relevance
“…As reported by previous studies (e.g. Aguilera et al, 2013aAguilera et al, , 2015Plaza-Bonilla et al, 2015;Abdalla et al, 2015), NT significantly increased the SOC content compared with CT (Table 3). This occurred despite the higher SOC content in the 15-30 cm layer in CT (as opposed to NT/MT), as suggested by Baker et al (2007).…”
Section: Global Warming Potentialsupporting
confidence: 85%
See 1 more Smart Citation
“…As reported by previous studies (e.g. Aguilera et al, 2013aAguilera et al, , 2015Plaza-Bonilla et al, 2015;Abdalla et al, 2015), NT significantly increased the SOC content compared with CT (Table 3). This occurred despite the higher SOC content in the 15-30 cm layer in CT (as opposed to NT/MT), as suggested by Baker et al (2007).…”
Section: Global Warming Potentialsupporting
confidence: 85%
“…The 'ASOC was the main cause of the differences between tillage and crop treatments (Fig. 4), while C02-eq emissions from inputs and operations were significant but less important, a finding which is consistent with Aguilera et al (2015) and Guardia et al (2016). Therefore, our results indicate that management practices which promote an increase in C stocks (e.g.…”
Section: Global Warming Potentialsupporting
confidence: 80%
“…No tillage system increased significantly C sequestration, which caused a significant decrease in Net-GWP in comparison with other tillage systems (MT and CT), as CO 2 -eq emissions for inputs and operations in NT system were lowest than MT/CT and less important due to a reduction in the number of labour operations. This finding was in agreement with Guardia et al (2016a) and Aguilera et al (2015). Results from a recent meta-analysis (Abdalla et al, 2015) concluded that NT system significantly reduced CO 2 -eq emissions and increased soil C stock particularly under arid and sandy soil conditions with low SOC content, supporting our findings.…”
Section: Effect Of Conservation Tillage On Ghg Emissions Under Meditesupporting
confidence: 92%
“…The 'ΔSOC' was the main cause of the differences between tillage and crop treatments (Fig. 5.4), while CO 2 -eq emissions from inputs and operations were significant but less important, a finding which is consistent with Aguilera et al (2015) and Guardia et al (2016a). Therefore, our results indicate that management practices which promote an increase in C stocks (e.g.…”
Section: Global Warming Potentialsupporting
confidence: 71%
See 1 more Smart Citation